New Predictors of Early and Late Outcomes after Primary Percutaneous Coronary Intervention in Patients with ST-Segment Elevation Myocardial Infarction and Unprotected Left Main Coronary Artery Culprit Lesion - Cãlin Homorodean; Adrian Corneliu Iancu; Daniel Leucuţa; Şerban Bãlãnescu; Ioana Mihaela Dregoesc; Mihai Spînu; Mihai Ober; Dan Tãtaru; Maria Olinic; Dan Bindea; Dan Olinic (Journal of Interventional Cardiology)
Objectives. The study evaluated the correlation between baseline SYNTAX Score, Residual SYNTAX Score, and SYNTAX Revascularization Index and long-term outcomes in ST-elevation myocardial infarction (STEMI) patients with primary percutaneous coronary intervention (PCI) on an unprotected left main coronary artery lesion (UPLMCA). Background. Previous studies on primary PCI in UPLMCA have identified cardiogenic shock, TIMI 0/1 flow, and cardiac arrest, as prognostic factors of an unfavourable outcome, but the complexity of coronary artery disease and the extent of revascularization have not been thoroughly investigated in these high-risk patients. Methods. 30-day, 1-year, and long-term outcomes were analyzed in a cohort of retrospectively selected, 81 consecutive patients with STEMI, and primary PCI on UPLMCA. Results. Cardiogenic shock (p=0.001), age (p=0.008), baseline SYNTAX Score II (p=0.006), and SYNTAX Revascularization Index (p=0.046) were independent mortality predictors at one-year follow-up. Besides cardiogenic shock (HR 3.28, p<0.001), TIMI 0/1 flow (HR 2.17, p=0.021) and age (HR 1.03, p=0.006), baseline SYNTAX Score II (HR 1.06, p=0.006), residual SYNTAX Score (HR 1.03, p=0.041), and SYNTAX Revascularization Index (HR 0.9, p=0.011) were independent predictors of mortality at three years of follow-up. In patients with TIMI 0/1 flow, the presence of Rentrop collaterals was an independent predictor for long-term survival (HR 0.24; p=0.049). Conclusions. In this study, the complexity of coronary artery disease and the extent of revascularization represent independent mortality predictors at long-term follow-up.